2019
DOI: 10.1123/ijsnem.2018-0031
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Intake in Australian Football Players: Sports Nutrition Knowledge and Macronutrient and Micronutrient Intake

Abstract: This study compared the energy, macronutrient, and micronutrient intake in elite and sub-elite Australian football players and compared nutritional intake to current recommendations. Sports nutrition knowledge was also quantified and compared between elite and sub-elite players. Nutritional intake was quantified in elite (n = 35) and sub-elite (n = 31) players using the Automated Self-Administered 24-Hour Dietary Assessment Tool. The 88-item Sports Nutrition Knowledge Questionnaire was used to quantify knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 48 publications
5
45
1
Order By: Relevance
“…Previous research has shown that Australian athletes have low NK scores 8,16-18 and fail to comply with best-practice sports nutrition guidelines. 19,20 As NK is one factor that can influence nutrition behaviour, 2,3 it is pertinent to explore the preferred information sources that athletes use, and how preferences influence NK. This is one of the first papers to investigate these topics in Australian team sports athletes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that Australian athletes have low NK scores 8,16-18 and fail to comply with best-practice sports nutrition guidelines. 19,20 As NK is one factor that can influence nutrition behaviour, 2,3 it is pertinent to explore the preferred information sources that athletes use, and how preferences influence NK. This is one of the first papers to investigate these topics in Australian team sports athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Data for previous sources of advice, preferred sources of nutrition information and preferred types of nutritioneducation support were assessed for the whole cohort and stratified based on age (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), ≥36 years), gender (male, female), level of education (high school, diploma and university), and level of sport played (elite, non-elite). Differences in these responses based on participant characteristics were assessed using χ 2 analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Carbohydrate requirements are reduced during low-intensity exercise of up to one hour (3–5 g⋅k −1 ⋅d −1 BM) [6]. Contrary to recommendations, previous studies have reported relatively low carbohydrate intakes in male AFL players (<5 g⋅kg −1 ⋅d −1 ) [5,7,8], and similar intakes have been identified in Australian female athletes from a range of individual and team sports [9]. While the recommended carbohydrate intake for high-intensity exercise is well established, the consistently reported low carbohydrate intake in team sport athletes may suggest that the physical demands of these sports require less carbohydrate than current recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…Adapting nutrient intake for current desired body weight or body composition is consistent with Jenner et al (2018) who stated that particularly around body composition assessment times in the AFL season, footballers were not meeting the daily nutrient intake guidelines. Lohman et al (2018) found that the majority of Australian footballers in their study over-consumed protein and under-consumed carbohydrate. The misunderstanding of nutrition advice revealed in our study is consistent with Lohman, Carr, and Condo (2018) and Trakman et al (2018) who found that Australian footballers' sports nutrition knowledge was "poor".…”
Section: Club Guidancementioning
confidence: 84%
“…Lohman et al (2018) found that the majority of Australian footballers in their study over-consumed protein and under-consumed carbohydrate. The misunderstanding of nutrition advice revealed in our study is consistent with Lohman, Carr, and Condo (2018) and Trakman et al (2018) who found that Australian footballers' sports nutrition knowledge was "poor".…”
Section: Club Guidancementioning
confidence: 84%